Synergistic Intercalation of Ethylene and Ethyl Methyl Carbonates with Tetrafluoroborate Anion into Graphite Electrode - Wang, Yunju (Langmuir : the ACS journal of surfaces and colloids, 2025)
Electrochemical intercalation behavior of anions into the graphite electrode is very complex, which can be governed by the solvation structure of the electrolyte in contact with the graphite electrode. Although extensive investigations have primarily focused on single-solvent electrolyte systems, the synergistic intercalation of multiple solvents with anions remains poorly understood. Herein, we demonstrate the synergistic intercalation of the tetrafluoroborate anion together with two different kinds of solvents, ethylene carbonate (EC) and ethyl methyl carbonate (EMC), from the solutions of LiBF4-EC/EMC into natural graphite. This intercalation process exhibits a unique continuous structural change of the anion-graphite intercalation compounds (AGICs), in stark contrast to the conventional two-phase transitions in AGICs. In situ X-ray diffraction (XRD) analysis reveals a progressive transition in AGICs with their intercalation gallery heights (IGHs) gradually contracting from 0.81 to 0.77 nm in a specific LiBF4-EC/EMC solution. The formation conditions of this synergistic cointercalation phenomenon have been systematically addressed